X - RAYING THE IMPACT OF DOMESTIC AND GLOBAL FACTORS ON STOCK RETURN VOLATILITY IN THE NIGERIAN STOCK MARKET - Okoli Margaret Nnenna (European Scientific Journal, ESJ, 2012)
The study evaluated the impact of domestic and global macroeconomic variables in explaining the movement of returns in the Nigerian stock market. It is an attempt to contribute to the unending search for relationship between stock market and macroeconomic variables on one hand and their volatilities. GARCH and VAR models were utilized to assess the impact of consumer price index, exchange rate, interest rate, money supply (M1 AND M2), industrial production index, federal funds rate and 6-month LIBOR on stock prices in Nigerian stock market. The empirical results revealed that the macroeconomic variables are significant in explaining movements in the stock prices and its volatility. Specifically it was confirmed that both the global and domestic factors are important in explaining the relationship between the stock returns and volatility implying that the Nigerian stock market is partially integrated debunking the controversy about which is more relevance- global or domestic factors.